Comparison of the effects of low level laser and insoles on pain, functioning, and muscle strength in subjects with stage 2 posterior tibial tendon dysfunction: A randomized study - Koltak, Cansu; Yurt, Yasin (Ios Press, 2021)
BACKGROUND: Low level laser therapy (LLLT) is known to be effective in tendinopathies. No study yet investigated the effect of LLLT on posterior tibial tendon dysfunction (PTTD) in comparison to orthotic treatment. OBJECTIVE: The aim was to compare the effects of LLLT and insole application on pain, function and muscle strength in subjects with stage 2 PTTD. METHODS: Fifty-two subjects with stage 2 PTTD were randomly assigned to the LLLT and insole groups. The foot pain, function and strength of invertor and evertor muscles of the subjects was evaluated before and after treatment, and after 9 months. RESULTS: Significant improvement was observed in the foot function and pain (p < 0.05) in both groups after treatment, but in the 9-month follow-up, the insole group had better values. The increase in 180 degrees.sec(-1) concentric invertor muscle strength was found significant after the treatment and in month-9 as compared to the initial values (p < 0.05). CONCLUSIONS: Both treatments are effective in reducing treating foot pain, as well as improving the function in subjects with stage 2 PTTD. However, at the end of the 9-month follow-up, it was seen that insoles were more effective. Neither method had a clinically important effect on muscle strength.
Keywords: Low level laser therapy; foot orthoses; posterior tibial tendon dysfunction